Ewolucja ikonostasu w sztuce cerkiewnej na terenie I Rzeczpospolitej - Janocha, Michał (TECHNE. Seria Nowa, 2018)
The article offers an outlook on the history and theology of the altar in the modern-period era in the context of the Byzantine Rite. In the Byzantine liturgy, the altar (prestoł) is separated from the nave by iconostasis which becomes a crucial structural and theological component of the Eastern Church. The time brackets for the paper are marked out by the Polish-Lithuanian Commonwealth (1569-1795). During that period, Orthodox art underwent the processes of the Westernisation of culture and the Latinisation of the liturgy, facilitated by the Union of Brest (1596). These factors resulted in the iconostasis gradually taking more Baroque forms, adapting certain elements of the reredos and becoming more alike (Photos 6-7), and eventually, in some 18th Century Orthodox churches, it was substituted with the Baroque reredos, which was particularly common in the territory of the Grand Duchy of Lithuania (Photos 8-10).It was an especially varied and diversified process. In Red Ruthenia and Subcarpathia, not only did the iconostasis not disappear, but it was also expanded, reaching its ‘classical’five-storey form in the second half of the 17th century (Photos 1-5). The aforementioned formal transformations were accompanied by liturgical changes, legitimised by the provisions of the Zamość Synod (1720). The article poses a question regarding the extent to which the form and the shape of the iconostasis were influenced by the Renaissance and Baroque reredoses within Polish churches. One can talk here about a purely formal influence, since a reredos in a church and an iconostasis within an Orthodox temple serve fundamentally different theological purposes.The reredos should emphasise the altar visually and ideologically (demonstratio et exposition), whereas the iconostasis is supposed to do the opposite, i.e. to cover and hide the altar (velatio et absconditio). What we encounter here are two extremes of Western and Eastern theology – the cataphatic one that aims at a positive depiction of the content of the Revelation and its systematic representation, and the apophatic one that accentuates the mystery of God which is inaccessible to the human mind. Naturally, both extremes coexist within Catholic and Orthodox theology, but – so to say – in reverse proportions. The iconostasis conceals the inconceivable mystery of the Eucharist and, at the same time, it reveals it through the very same cover. The metaphor of the window, used in the title of the Łodź-held conference, was derived from the theology of iconostasis by Father Pavel Florensky. The physical wall of the iconostasis is a symbolic boundary between Heaven and Earth, a boundary that unites and divides at the same time. Without windows, this wall would be solid. And in these windows stand Christ, Mary and the saints – those who once walked the earth and who now live somewhere else. And it is through them that the mystical light falls upon the faithful. They participate in the heavenly liturgy, the echo and reflection of which is the earthly liturgy. They stand at the border of two worlds in order to testify that Heaven does exist. This article is a preliminary attempt to systematise Ukrainian and Belarusian iconostases in their historical development, on the basis ofobjects preserved or known from the source contentand existing research results. This article was written alongside a profound iconographic research conducted by the author, presented in the book entitled Ukrainian and Belarusian Festive Icons in the former Polish Republic. The Issue of Canon (Ukraińskie i białoruskie ikony świąteczne w dawnej Rzeczypospolitej. Problem kanonu, Warsaw: Neriton 2001) and expanded in the article published under the following title: Iconostases in Orthodox Temples of the Polish Republic in the 17th and 18th Centuries (Ikonostasy w cerkwiach Rzeczypospolitej w XVII i XVIII wieku, “PrzeglądWschodni”Issue No. 8 (2003), Vol. 4 (32), pp. 897-921).